2021
DOI: 10.1017/cts.2021.27
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and lessons learned for institutional review board procedures during the COVID-19 pandemic

Abstract: This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 4 publications
2
23
0
Order By: Relevance
“…Other delays may be explained by changes to IRB policies as the research landscape shifted during the COVID-19 pandemic. Consistent with our experiences, research has shown that IRB offices were prioritizing reviews of COVID-related research and changes in protocols for research that was shifting from in-person to online [26]. However, it should be noted that not all delays were caused by the COVID-19 pandemic as 9 of the 21 (43%) institutions that began the sIRB process prior to the onset of the COVID-19 pandemic in the USA were onboarded to the sIRB before March 2020.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Other delays may be explained by changes to IRB policies as the research landscape shifted during the COVID-19 pandemic. Consistent with our experiences, research has shown that IRB offices were prioritizing reviews of COVID-related research and changes in protocols for research that was shifting from in-person to online [26]. However, it should be noted that not all delays were caused by the COVID-19 pandemic as 9 of the 21 (43%) institutions that began the sIRB process prior to the onset of the COVID-19 pandemic in the USA were onboarded to the sIRB before March 2020.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with our experiences, research has shown that IRB offices were prioritizing reviews of COVID-related research and changes in protocols for research that was shifting from in-person to online. 26 However, it should be noted that not all delays were caused by the COVID-19 pandemic as 9 of the 21 (43%) institutions that began the sIRB process prior to the onset of the COVID-19 pandemic in the United States were onboarded to the sIRB before March 2020. We were also surprised that some institution IRBs administered detailed reviews rather than abbreviated reviews prior to or even after ceding to a single IRB.…”
Section: Discussionmentioning
confidence: 99%
“…centers (AMCs). For example, electronic case report forms and consents are now standard operating procedures while regulatory processes have been streamlined and harmonized to maximize productivity and improve safety [12,13].…”
Section: A Phased Reopeningmentioning
confidence: 99%
“…Some of the ethics issues identified in this study align with COVID-19 literature around virtual informed consent and the need to stay up to date with published data during an evolving pandemic to inform study designs 32,39 . During the Ebola outbreak, different ethics issues were raised in review of protocols such as on storage of blood samples for future use and the exclusion of pregnant women in clinical trials 30 .…”
Section: Discussionmentioning
confidence: 73%
“…Joint review is described as a way of streamlining different review processes into a single comprehensive review with multiple bodies to expedite time to study implementation 30,31 . A process similar to joint review described for ethics review committees in the United States of America during COVID-19 was perceived to improve overall review efficiency 32 . Other than the reported successes of the WHO's Africa Vaccine Regulatory Forum 33 , there is little evidence of joint review in previous health emergencies in low resource settings.…”
Section: Discussionmentioning
confidence: 99%